Decoy Receptor 3 Promotes Preosteoclast Cell Death via Reactive Oxygen Species-Induced Fas Ligand Expression and the IL-1α/IL-1 Receptor Antagonist Pathway - Yi-Jen Peng; Ching-Tsung Peng; Yi-Hsuan Lin; Gu-Jiun Lin; Shing-Hwa Huang; Shyi-Jou Chen; Huey-Kang Sytwu; Chia-Pi Cheng (Hindawi Limited, 2020)
Purpose. Interleukin-1α (IL-1α) is a potent cytokine that plays a role in inflammatory arthritis and bone loss. Decoy receptor 3 (DCR3) is an immune modulator of monocytes and macrophages. The aim of this study was to investigate the mechanism of DCR3 in IL-1α-induced osteoclastogenesis. Methods. We treated murine macrophages with DCR3 during receptor activator of nuclear factor kappa Β ligand- (RANKL-) plus IL-1α-induced osteoclastogenesis to monitor osteoclast formation by tartrate-resistant acid phosphatase (TRAP) staining. Osteoclast activity was assessed using a pit formation assay. The mechanisms of inhibition were studied by biochemical analyses, including RT-PCR, immunofluorescent staining, flow cytometry, an apoptosis assay, immunoblotting, and ELISA. Results. DCR3 suppresses IL-1α-induced osteoclastogenesis in both primary murine bone marrow-derived macrophages (BMM) and RAW264.7 cells as it inhibits bone resorption. DCR3 induces RANKL-treated osteoclast precursor cells to express IL-1α, secretory IL-1ra (sIL-1ra), intracellular IL-1ra (icIL-1ra), reactive oxygen species (ROS), and Fas ligand and to activate IL-1α-induced interleukin-1 receptor-associated kinase 4 (IRAK4). The suppression of DCR3 during RANKL- or IL-1α-induced osteoclastogenesis may be due to the abundant secretion of IL-1ra, accumulation of ROS, and expression of Fas ligand in apoptotic osteoclast precursor cells. Conclusions. We concluded that there is an inhibitory effect of DCR3 on osteoclastogenesis via ROS accumulation and ROS-induced Fas ligand, IL-1α, and IL-1ra expression. Our results suggested that the upregulation of DCR3 in preosteoclasts might be a therapeutic target in inflammatory IL-1α-induced bone resorption.